Леонардо да Винчи - Санти Бруно (Великие мастера итальянского искусства, 1997)
Экземпляры: аб. (1999) / Инвентарный номер: 41538 / Цена: / Сис.шифр: 85.103(4Ит)4-8 / Авт.знак: С 18 / ГРНТИ: 18.31 / ББК: 85.103(4Ит)4-8 Леонардо да Винчи я6